Where men hide - Twitchell, James B., 1943- (Columbia University Press, 2006)
Where Men Hide is a spirited tour of the dark and often dirty places men go to find comfort, camaraderie, relaxation, and escape. Ken Ross's striking photographs and James Twitchell's lively analysis trace the evolution of these virtual caves, and question why they are rapidly disappearing. Ross documents both traditional and contemporary male haunts, such as bars, barbershops, lodges, pool halls, strip clubs, garages, deer camps, megachurches, the basement Barcalounger, and Twitchell examines their provenance, purpose, and appeal. -- BOOK JACKET.